Non-intrusive method for monitoring battery conditions in electric buses - Muhammad Aidil Bin Norshaid (Nanyang Technological University, 2023)
This paper proposes a non-intrusive method for monitoring battery conditions in electric buses. The method uses data obtained from the electric buses’ Battery Management System. The proposed method is non-intrusive, as it does not require any additional sensors or hardware to be installed in the bus, reducing the cost and complexity of battery monitoring systems. The effectiveness of the proposed method is evaluated through experiments on real-world electric buses, and the results demonstrate that the method can accurately estimate the battery's state of charge and state of health in real time. The proposed method has the potential to improve the reliability and safety of electric bus operations by providing operators with real-time information on battery conditions, enabling proactive maintenance and reducing the risk of unexpected battery failures.